ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR ALAS KAKI INDONESIA KE AMERIKA SERIKAT - NAYAH MARIATI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study was conducted to determine Factors Affecting Indonesia’s footwear export to the United States and to know which variables are most influential on footwear exports.The location of this research is in Indonesia, and the data source used is secondary data obtained from The Indonesian Central Bureau of Statistics, World Bank, and Bank Indonesia where the data are analyzed using multiple linear regression model to determine whether the variables of footwear export such as exchange rate, the gross domestic product of the United States, and the inflation set affect to  the export of Indonesian footwear.The results of this study indicate that the variables of exchange rate, US GDP, and inflation simultaneously have significant effect on the export of Indonesia’s footwear that can seen from the test f that obtained significant value. Partial test of variable of exchange rate and inflation show insignificant result because when exchange rate or inflation weaken price will rise hence export will decrease, but the price of the competitor's country exports also increases, the price of Indonesian goods becomes less expensive and export destination countries of Indonesia will continue to purchase products while for US GDP variables showed significant results because when the United States income increased then the purchasing power of the community also increased and positively affected the export of footwear. Keywords: Export of Footwear, Exchange Rate, Gross Domestic Product of United States of America, Inflation